2020
DOI: 10.1371/journal.pone.0233209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of respiratory motion correction on lesion visibility and quantification in thoracic PET/MR imaging

Abstract: The impact of a method for MR-based respiratory motion correction of PET data on lesion visibility and quantification in patients with oncologic findings in the lung was evaluated. Twenty patients with one or more lesions in the lung were included. Hybrid imaging was performed on an integrated PET/MR system using 18 F-FDG as radiotracer. The standard thoracic imaging protocol was extended by a free-breathing self-gated acquisition of MR data for motion modelling. PET data was acquired simultaneously in list-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…With the introduction of motion correction averaging to further improve the imaging performance of MRI through post processing [23,24], as well as superior soft tissue contrast compared to CT, the radial VIBE sequence should be considered for further investigation in patient studies.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of motion correction averaging to further improve the imaging performance of MRI through post processing [23,24], as well as superior soft tissue contrast compared to CT, the radial VIBE sequence should be considered for further investigation in patient studies.…”
Section: Discussionmentioning
confidence: 99%
“…Besides attenuation correction, physiological motion can have a severe impact on the obtained image quality. Motion correction with motion models derived from other imaging modalities or surrogate measures [39][40][41][42][43][44][45][46][47] can be integrated [48] to compensate for motion-induced blurring and aliasing in PET.…”
Section: Machine Learning-based Processing and Analysis Of Multiparam...mentioning
confidence: 99%
“…Another study reported that after motion correction, an additional lesion was identified in the liver [ 77 ]. More specifically in a recent investigation concentrated on patients with lung lesions, the readers scored lesions in the motion corrected images with 38% and 56% more confidence compared to the non-corrected images and gated images, respectively ( figure 4 ) [ 78 ].
Figure 3 [ 18 F]FDG PET-MRI study.
…”
Section: Applications Of Motion Correctionmentioning
confidence: 99%
“…Note the enhanced sharpness and signal-to-noise ratio of the hilar lesion in the motion corrected data in comparison to the other two methods, while the bone lesion in the region with less motion varies less between the uncorrected and motion compensated reconstructions (Reproduced from Gratz M, Ruhlmann V, Umutlu L, Fenchel M, Hong I, Quick HH (2020) Impact of respiratory motion correction on lesion visibility and quantification in thoracic PET/MRI imaging. PLoS ONE 15 , e0233209) [ 78 ]. (Online version in colour.)…”
Section: Applications Of Motion Correctionmentioning
confidence: 99%